Changes of energy fluxes in marine animal forests of the Anthropocene: factors shaping the future seascape. (1st August 2019) - Rossi, Sergio; Isla, Enrique; Bosch-Belmar, Mar; Galli, Giovanni; Gori, Andrea; Gristina, Michele; Ingrosso, Gianmarco; Milisenda, Giacomo; Piraino, Stefano; Rizzo, Lucia; Schubert, Nadine; Soares, Marcelo; et al.
Abstract: Climate change is already transforming the seascapes of our oceans by changing the energy availability and the metabolic rates of the organisms. Among the ecosystem-engineering species that structure the seascape, marine animal forests (MAFs) are the most widespread. These habitats, mainly composed of suspension feeding organisms, provide structural complexity to the sea floor, analogous to terrestrial forests. Because primary and secondary productivity is responding to different impacts, in particular to the rapid ongoing environmental changes driven by climate change, this paper presents some directions about what could happen to different MAFs depending on these fast changes. Climate change could modify the resistance or resilience of MAFs, potentially making them more sensitive to impacts from anthropic activities (i.e. fisheries and coastal management), and vice versa, direct impacts may amplify climate change constraints in MAFs. Such changes will have knock-on effects on the energy budgets of active and passive suspension feeding organisms, as well as on their phenology, larval nutritional condition, and population viability. How the future seascape will be shaped by the new energy fluxes is a crucial question that has to be urgently addressed to mitigate and adapt to the diverse impacts on natural systems.